A nationwide parent survey of antibiotic use in Australian children. (26th February 2020) - Anderson, Rebecca; Rhodes, Anthea; Cranswick, Noel; Downes, Marnie; O'Hara, Jonathan; Measey, Mary-Anne; Gwee, Amanda
Abstract: Background: Antimicrobial resistance is increasing globally, largely due to high rates of antibiotic use and misuse. Factors that influence frequent antibiotic use in children are poorly understood. Objectives: This study describes rates of antibiotic use in Australian children and investigates parental factors including knowledge, attitudes and behaviours that influence antibiotic use. Methods: An online questionnaire relating to antibiotic use was administered as part of the Royal Children's Hospital National Child Health Poll to a randomly recruited nationwide sample of parents or guardians of children aged 0–17 years in Australia. Data on antibiotic use in children and parental knowledge of appropriate indications for antibiotics and behaviours were collected. Standard binary logistic regression was used to assess associations between parent demographics and behaviour with antibiotic administration. Results: The survey was completed by 2157 parents (64% completion rate), of which 1131 (52%) reported having given oral antibiotics to one or more of their children in the preceding 12 months. Of the 3971 children represented overall, 1719 (43%) had received at least one course of antibiotics. The average number of courses per child was 0.86 overall and 1.96 courses per child among those with reported antibiotic use. Notably, 194/1131 (17%) parents reported giving antibiotics to their child without a prescription. Poor parental knowledge of antibiotic indications was associated with antibiotic use. Conclusions: Reducing excessive use of antibiotics in children is necessary in the global strategy for preventing antimicrobial resistance. This study identified areas for public health interventions to educate parents and increase regulation of access to antibiotics.